The Characteristics of the Lexis in the Public Addresses of Some Prominent Figures in the Republic of Macedonia - Biljana Malenko (Ksiegarnia Akademicka Publishing, 2014)
The language as a means of communication is used for various purposes. The best example for that is the public discourse. It was an incentive to analyse the lectures, speeches and public appearances of public figures from the contemporary aspect. It is about fifteen texts from: Metodija Andonov‑Cento, Panko Brashnarov, Blazhe Koneski, Stojan Andov, Nikola Kljusev, Kiro Gligorov, Branko Crvenkovski, Ljupco Georgievski, Boris Trajkovski, Luan Starova, Goran Stefanovski, Srgjan Kerim, Nikola Gruevski i Gjorgje Ivanov, published in the book First Anthology of the Greatest Speeches of All Times from the World and Macedonia. Although public speeches can be analysed from different aspects, we will focus on some aspects of stylistic expressiveness of the speeches. From lexical perspective, the emphasis is on the use of international lexis, which, as known, is of Latin or Greek origin and has entered the language mainly from the English language. The presence of this lexis is characteristic for other languages as well, which means that it is a reality without which the contemporary languages cannot function, so as the Macedonian. Still, there is a need for folklore words, dialects, archaisms, jargons and poetic function, maybe as an antithesis of the increased presence of the international lexis. The public speeches in this anthology are chosen as important, not only for their content with utter messages in the time of particular social happenings, but also for the manner of their representation. That is the reason why they stay in the collective memory of the Macedonian people.